Course of Duration and Trigger Factors of Vertigo Attacks in Patients with Benign Recurrent Vertigo, Menière’s Disease, or Vestibular Migraine - Uijttewaal, Maarten C.; van Leeuwen, Roeland B.; Colijn, Carla; Schermer, Tjard R. (Audiology & neurotology, 2024)
Introduction: Benign recurrent vertigo (BRV), Menière’s disease (MD), and vestibular migraine (VM) show many similarities with regard to the course of vertigo attacks and clinical features. In this paper, we elaborate on the decreasing frequency of vertigo attacks observed in a previous study from our group by exploring changes in the duration and trigger factors of vertigo attacks in patients with BRV, MD, or VM. Methods: For this 3-year prospective cohort study in our tertiary referral center we recruited patients with a confirmed diagnosis of BRV, MD, or VM by a neurologist and otorhinolaryngologist in our center in 2015–2016. A study-specific questionnaire was used to assess the usual duration of vertigo attacks and their potential triggers every 6 months. Main outcome measures were changes in duration and trigger factors of vertigo attacks in the subgroups of patients with persisting attacks, which were analyzed using repeated measures logistic regression models. Results: 121 patients were included (BRV: n = 44; MD: n = 43; VM: n = 34) of whom 117 completed the 3-year follow-up period and 57 (48.7%) kept reporting vertigo attacks at one more follow-up measurements. None of the diagnosis groups showed statistically significant shortening of attack duration at the subsequent annual follow-up measurements compared to baseline. At baseline, stress and fatigue being reported as triggers for attacks differed significantly between the three groups (stress: BRV 40.9%, MD 62.8%, VM 76.5%, p = 0.005; fatigue: BRV 31.0%, MD 48.8%, VM 68.8%, p = 0.003). In the VM group, a consistent reduction of stress and fatigue as triggers was observed up until the 24- and the 30-month follow-up measurements, respectively, with odds ratios (ORs) ranging from 0.15 to 0.33 (all p < 0.05). In the MD group, a consistent reduction of head movements as trigger was observed from the 24-month measurement onward (ORs ranging from 0.07 to 0.11, all p < 0.05). Conclusion: Our study showed no reduction in vertigo attack duration over time in patients with BRV, MD, and VM who remain to have vertigo attacks. In VM and MD patients with persisting vertigo attacks stress, fatigue and head movements became less predominant triggers for vertigo attacks.